A qualitative study of the role of workplace and interpersonal trust in shaping service quality and responsiveness in Zambian primary health centres. Issue 2 (20th May 2015) - Topp, Stephanie M; Chipukuma, Julien M
Abstract : Background: Human decisions, actions and relationships that invoke trust are at the core of functional and productive health systems. Although widely studied in high-income settings, comparatively few studies have explored the influence of trust on health system performance in low- and middle-income countries. This study examines how workplace and inter-personal trust impact service quality and responsiveness in primary health services in Zambia. Methods: This multi-case study included four health centres selected for urban, peri-urban and rural characteristics. Case data included provider interviews (60); patient interviews (180); direct observation of facility operations (two weeks/centre) and key informant interviews (14) that were recorded and transcribed verbatim. Case-based thematic analysis incorporated inductive and deductive coding. Results: Findings demonstrated that providers had weak workplace trust influenced by a combination of poor working conditions, perceptions of low pay and experiences of inequitable or inefficient health centre management. Weak trust in health centre managers' organizational capacity and fairness contributed to resentment amongst many providers and promoted a culture of blame-shifting and one-upmanship that undermined teamwork and enabled disrespectful treatment of patients. Although patients expressed a high degree of trust in health workers' clinical capacity, repeated experiences of disrespectful or unresponsive care undermined patients' trust in health workers' service values and professionalism. Lack of patient–provider trust prompted some patients to circumvent clinic systems in an attempt to secure better or more timely care. Conclusion: Lack of resourcing and poor leadership were key factors leading to providers' weak workplace trust and contributed to often-poor quality services, driving a perverse cycle of negative patient–provider relations across the four sites. Findings highlight the importance of investing in both structural factors and organizational management to strengthen providers' trust in their employer(s) and colleagues, as an entry-point for developing both the capacity and a work culture oriented towards respectful and patient-centred care.